Phytonymic Pejorative Names for Men in the Pirot Speech (Linguocultural Aspect) - Ratković , Dragana M. (Slavistica Vilnensis, 2021)
The subject of the paper are nouns and noun phrases of negative expressive tonality, which primarily name realities from the plant world (plants and their parts, terms related to wood processing), and secondarily people in the Pirot dialect. The analysis also includes derivatives of units that belong to the semantic field “phytonym” and noun phrases whose adjective has a phytonymic meaning. The corpus consists of two dictionaries of the Pirot dialect: Novica Živković [Živković 1987] and Dragoljub Zlatković [Zlatković 2014; 2017]. The author analyzes language units from the linguocultural aspect to answer the questions related to: (1) human characteristics, behaviors and actions in Pirot speech which initiate negative characterization of a person with a phytonymic pejoratives; (2) appointments that reveal evaluation parameters; (3) the relationship between pejoration and laudation on the material of botanical vocabulary and terminology in naming the man in the Pirot dialect and (4) the relation of the phytonymic pejoration of man in the Pirot dialect with the same names in the modern Serbian language. Such a methodological procedure enables (1) reconstruction of the conceptualization of man as a plant outlined by phytonymic pejoratives in the linguistic picture of the world and in the traditional culture of the Pirot region, as well as (2) consideration of relations and determination of (in) similarity with the image of the world in the modern Serbian language developed by the same lexical-semantic means.